2019
DOI: 10.1038/s41467-019-11231-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of cytoplasmic dynein tension sensing

Abstract: Cytoplasmic dynein is the most complex cytoskeletal motor protein and is responsible for numerous biological functions. Essential to dynein’s function is its capacity to respond anisotropically to tension, so that its microtubule-binding domains bind microtubules more strongly when under backward load than forward load. The structural mechanisms by which dynein senses directional tension, however, are unknown. Using a combination of optical tweezers, mutagenesis, and chemical cross-linking, we show that three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
134
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(142 citation statements)
references
References 69 publications
7
134
1
Order By: Relevance
“…The activity of dynein is also regulated by applied forces (Figure 1D). Several biophysical studies have shown that dynein has a characteristic force response property: it binds to a microtubule more strongly in the presence of backward loads than forward loads (Cleary et al, 2014;Nicholas et al, 2015a;Rao et al, 2019). Recently, Rao et al (2019) revealed that the asymmetric force response to directional loads is mediated by the sliding of the coiled-coils of the stalk, and that coordinated conformational changes of linker regions control this process.…”
Section: Layer 4: Regulation By External Forcesmentioning
confidence: 99%
“…The activity of dynein is also regulated by applied forces (Figure 1D). Several biophysical studies have shown that dynein has a characteristic force response property: it binds to a microtubule more strongly in the presence of backward loads than forward loads (Cleary et al, 2014;Nicholas et al, 2015a;Rao et al, 2019). Recently, Rao et al (2019) revealed that the asymmetric force response to directional loads is mediated by the sliding of the coiled-coils of the stalk, and that coordinated conformational changes of linker regions control this process.…”
Section: Layer 4: Regulation By External Forcesmentioning
confidence: 99%
“…Based on the modeled conformational changes of MTBD in the absence and presence of MTs in the present study, we propose that the mechanochemical cycle of dynein proceeds via two distinctive pathways, namely an "ATPase-driven pathway" and a "MT-binding-induced pathway". In the ATP-bound states, the stalk coiled-coil adopts the +β-registry across the entire region following the linker detachment from AAA5 ( Fig.6b (2)), and MTBD is stabilized in the low-affinity state 8 (Fig. 6b (3)).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies have demonstrated that the sliding of CC1 with respect to CC2 by oneturn of an α−helix results in a distinctive change in the affinity for MTs 18,19 . A recent single-molecule study further demonstrated that the sliding of coiled-coil helices and the resulting changes in interaction with stalk and strut/buttress regulates the MT-binding affinity and dynein motility 8 . Comparison of the crystal structures of the motor domain in the ADP/Vi- 11 and ADP 9 -bound states have indicated that the change in the registry is caused by an altered interaction between the stalk and strut/buttress.…”
mentioning
confidence: 99%
See 2 more Smart Citations